Association between Maternal Characteristics and Maternal Capabilities: A Quantitative Study in The Special Region of Yogyakarta - Siti Nurunniyah; Fatimatasari; Dyah Pradnya Paramita; Claudia Banowati Subarto; Fatikha Khoirun Nisa; Asusan; Vera Tasya Ashari; Patricia Sator (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: The Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are still high in Indonesia due to various causal factors. Mothers play a crucial role in improving family health. Maternal capabilities are an important factor in fulfilling their role in maintaining family health. The overview of maternal capabilities in Indonesia is not yet known. Given the limited research on maternal capabilities in Indonesia, it is necessary to examine the relationship between demographic characteristics and maternal capabilities to identify the factors that affect them.   This study aimed to explore the relationship between demographic characteristics and maternal capabilities. Method: This study uses a quantitative, cross-sectional design. Sampling in this study uses a consecutive sampling technique with a total of 211 respondents. The research instrument used questionnaires. The analysis uses the chi-square test and logistic regression. Result: Education level and place of residence were significantly associated with maternal capabilities (p < 0.05), whereas level of income, age, and parity showed no significant association. Mothers with >12 years of education and those residing in urban areas were 2.6 and 1.8 times more likely, respectively, to demonstrate strong maternal capabilities. Poor mental health is the highest prevalence indicator of all indicators of maternal capability, with a percentage of 28.4%. Conclusion: There is a relationship between education level and place of residence with maternal capabilities. Maternal capabilities may be enhanced by targeted interventions in education and health promotion programs, especially in rural areas.